Meeting Milestones: Results of a Quality-Improvement Curriculum to Achieve Cost-Conscious Care. Issue 1 (1st January 2018) - Chang, Olivia; Jordan, JoAnn; Shah, Neel; Mendiola, Monica; Merport Modest, Anna; Golen, Toni
ABSTRACT: There is a lack of residency education in cost-conscious care. We implemented a costing and quality improvement (QI) curriculum to Obstetrics and Gynaecology trainees using "Time-Driven Activity-Based Costing (TDABC), " and assessed its educational impact. The curriculum included didactic and practical portions. Pre-and post-knowledge surveys were obtained from 24 residents on self-perceived knowledge of key QI principles. Self-perceived knowledge, before and after the curriculum, was scored on a Likert scale from 0 to 5 points (0 is the least knowledge and 5 is the most knowledge). The mean scores reported an increase in knowledge of clinical guideline development (pre = 1.19 vs. post = 3.07, p  = 0.0052); confidence in participating in QI work (pre = 1.75 vs. post = 3.42 points, p  < 0.0001); and knowledge in communicating QI principles (pre = 1.89, post = 3.17, p  < 0.0003). Our educational programme uses the TDABC method and the residents' clinical experience effectively to teach residents cost-conscious care.